2020
DOI: 10.3390/biom10091277
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3: A Potential Prognostic and Diagnostic Marker for Heart Disease and Detection of Early Stage Pathology

Abstract: The use of molecular biomarkers for the early detection of heart disease, before their onset of symptoms, is an attractive novel approach. Ideal molecular biomarkers, those that are both sensitive and specific to heart disease, are likely to provide a much earlier diagnosis, thereby providing better treatment outcomes. Galectin-3 is expressed by various immune cells, including mast cells, histiocytes and macrophages, and plays an important role in diverse physiological functions. Since galectin-3 is readily ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 115 publications
1
38
0
10
Order By: Relevance
“…Indeed, prior studies have observed an association between total body fat and Gal-3 levels (86). Although the sex-specific prognostic value of Gal-3 in HF remains unknown, baseline Gal-3 concentrations were associated with adverse outcomes during follow-up in patients with acute and chronic HF (87)(88)(89). However, the prognostic value of Gal-3 in the setting of chronic HF remains controversial; other biomarkers, such as NT-proBNP or sST2, have frequently exhibited superior predictive value (90).…”
Section: Galectin-3mentioning
confidence: 99%
“…Indeed, prior studies have observed an association between total body fat and Gal-3 levels (86). Although the sex-specific prognostic value of Gal-3 in HF remains unknown, baseline Gal-3 concentrations were associated with adverse outcomes during follow-up in patients with acute and chronic HF (87)(88)(89). However, the prognostic value of Gal-3 in the setting of chronic HF remains controversial; other biomarkers, such as NT-proBNP or sST2, have frequently exhibited superior predictive value (90).…”
Section: Galectin-3mentioning
confidence: 99%
“…Galectins are a family of‐galactoside binding proteins involved in the regulation of the interactions for “cell‐to‐cell” and “cell‐to‐matrix” in different tissues and organs 2 . In galectin‐3, ≈30 kDa chimera‐type galectin is widely expressed by monocytes/macrophages, natural killer cells, activated T and B cells, dendritic cells, mast cells, eosinophils, epithelial cells, endothelial cells, osteoblasts, and osteoclasts in various human tissues 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Several researches have indicated that galectin‐3 is associated with different diseases including autoimmune disease, heart diseases, diabetes mellitus, renal diseases, viral infections, and tumors 3,4 . In the literature, it has been stated that galectin‐3 is a useful biomarker in the early detection of various diseases such as acute myocarditis, acute myocardial infarction, cardiac fibrosis, glioma tumorigenesis, and rheumatoid arthritis (RA) 2,6 . There is no information that reveals the association between galectin‐3 and periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…Gal-3 levels have been shown to increase in pre-symptomatic HF animal models as well as during HF progression in both animal models and humans [ 26 , 27 ]. Nevertheless, the use of Gal-3 as a biomarker for asymptomatic LV dysfunction is still debated, mainly due to its low specificity [ 27 ]. In fact, because Gal-3 is not organ-specific, the increase of its concentration in plasma could be the consequence of several inflammatory and fibrotic processes in organs other than the heart.…”
Section: Current and Emerging Protein Biomarkersmentioning
confidence: 99%